Analisis Wilayah Nodal Berdasarkan Analisis Hierarki Wilayah di Kabupaten Malang: Nodal Area Analysis based on Regional Hierarchical Analysis in Malang Regency - Dewi Ranggana; Wasrob Nasrudin (Politeknik Pertanian Bogor, 2021)
The development of the Malang Regency area with the largest population in East Java needs to be considered. The existence of a regional hierarchy by assessing aspects of the population as well as the existing facilities and infrastructure in each sub-district is able to see the center of growth and optimize the potential of the region, especially in the agricultural sector. and infrastructure for each sub-district, determine the capital and hinterland areas, and plan regional development with an agribusiness system approach. The research method uses data collection techniques and secondary data analysis sourced from BPS (Central Bureau of Statistics) and the Ministry of Education and Culture. The results of the regional hierarchical analysis show that Singosari District occupies the highest hierarchy as the core or center of regional development, with various factors such as population, number of facilities, transportation, and historical value. The hinterland area is divided into three divisions based on the comparative analysis of the population and the number of facilities and infrastructure in each sub-district. Determination of regional development centers with this analysis, focused on each agribussines subsystem with an emphasis on superior products of each region and creative marketing as well as optimizing regional development plans that are tailored to the region itself.